Carbon nanotubes enhanced bimorph effect of U-shaped flexure cantilever beam actuators made from polyethylene terephthalate and polymethyl methacrylate. (1st December 2022) - Tsai, Hsin-Jung; Chang, Huang-Chao; Yang, Yung-Kai; Hsu, Wen-Kuang
Abstract: U-shaped cantilever actuators made from PET and PMMA exhibit a bimorph effect upon radiation heating and beam always moves toward PMMA side with maximum displacement and displacing rate measured to be 2100 μ m and 35 μ m s −1 . This number increases to 3300 μ m and 55 μ m s −1 while PET surfaces are coated with single-walled carbon nanotubes acting as heat reservoir. Actuations can be further improved by carbon nanotube resistive heating and improvement reaches two-fold (4100 μ m and 68.3 μ m s −1 ). Coated beam actuators exhibit an excellent stability over 2 h intermittent operations where the maximum displacement varies only in ±1%.